Возраст третьей любви: роман / Анна Берсенева - Берсенева Анна (Русский характер, 2014)
Экземпляры: ф. 3 (20150205) / Инвентарный номер: 49623 / Цена: 87.00 / Авт.знак: Б 51 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4